2003
DOI: 10.1038/sj.bjc.6601283
|View full text |Cite
|
Sign up to set email alerts
|

First-line gemcitabine with cisplatin or epirubicin in advanced non-small-cell lung cancer: a phase III trial

Abstract: The purpose of our study was to compare progression-free survival and quality of life (QOL) after cisplatin -gemcitabine (CG) or epirubicin -gemcitabine (EG) in chemotherapy-naive patients with unresectable non-small-cell lung cancer. Patients (n ¼ 240) were randomised to receive gemcitabine 1125 mg m À2 (days 1 and 8) plus either cisplatin 80 mg m À2 (day 2) or epirubicin 100 mg m À2 (day 1) every 3 weeks for a maximum of five cycles. Eligible patients had normal organ functions and Eastern Cooperative Oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 36 publications
(43 reference statements)
1
30
0
Order By: Relevance
“…The response rate was 50% and median survival was 8 months in that study. Combinations of HDEpi with vinorelbine [21, 22] and gemcitabine [23] also yielded comparable response rates and survival times.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate was 50% and median survival was 8 months in that study. Combinations of HDEpi with vinorelbine [21, 22] and gemcitabine [23] also yielded comparable response rates and survival times.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these 18 trials, only 2 had HRQoL as a primary endpoint [37,50] and just 1 of these included statistical analyses of HRQoL data [37]. Of the remaining 16 trials, 8 reported statistical analysis data on lung-cancerrelated symptoms [36,[38][39][40]43,45,46,48,49].…”
Section: Overview Of Trials and Compliancementioning
confidence: 98%
“…Of these, 2 used LCSS [21,36], 12 used EORTC QLQ-C30/LC13 [37][38][39][40][41][42][43][44][45][46][47][48][49], and 4 used FACT-L [50][51][52][53][54]. Out of these 18 trials, only 2 had HRQoL as a primary endpoint [37,50] and just 1 of these included statistical analyses of HRQoL data [37].…”
Section: Overview Of Trials and Compliancementioning
confidence: 99%
“…All other societies recommend first-line platinum-based chemotherapy for advanced NSCLC patients. There are multiple randomised published trials on this topic [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. In terms of survival, there is no statistically significant difference between the two types of treatment in all but one trial.…”
Section: Lung Cancer Chemotherapy J-p Sculier and D Moro-sibilotmentioning
confidence: 99%